Odpowiedzi

2010-02-10T18:19:53+01:00
1.
a) 3(a-2)= 3a-6

b) -4(x+y)= -4x-4y

c) -5(-x+1)= 5x-5

d) m(2m+3)= 2m²+3m

e) xy(2x-3y+5)= 2x²y-3xy²+5xy

f) k(3l+2m)= 3kl+2km

g) -p(r-5s)= -pr+5ps
2010-02-10T18:20:07+01:00
A) 3(a-2)=3a-6
b) -4(x+y)=-4x-4y
c) -5(-x+1)=5x-5
d) m(2m+3)=2m²+3m
e) xy(2x-3y+5)=2x²y-3xy²+5xy
f) k(3l+2m)=3kl+2km
g) -p(r-5s)=-pr+5ps
  • Użytkownik Zadane
2010-02-10T18:23:14+01:00
A) 3(a-2)=3a-6
b) -4(x+y)=-4x-4y
c) -5(-x+1)=5x-5
d) m(2m+3)=2m²+3m
e) xy(2x-3y+5)=2x²y-3xy²+5xy
f) k(3l+2m)=3kl+2km
g) -p(r-5s)=-pr+5ps